Clinical outcomes and predictors of technical failure of endoscopic transpapillary gallbladder drainage in acute cholecystitis. (4th March 2023) - Sato, Junya; Nakahara, Kazunari; Michikawa, Yosuke; Morita, Ryo; Suetani, Keigo; Sekine, Akihiro; Igarashi, Yosuke; Kobayashi, Shinjiro; Otsubo, Takehito; Itoh, Fumio
Abstract: Background and aims: Endoscopic transpapillary gallbladder drainage (ETGBD) has been performed as an alternative therapy against cholecystectomy in patients with acute cholecystitis. To date, few studies have reported the safety, efficacy, and factors affecting ETGBD. We evaluated the clinical outcomes and predictors of technical failure of ETGBD. Methods: Patients with acute cholecystitis who underwent ETGBD were retrospectively reviewed, and consecutive patients were included in the study. The technical success rate, clinical success rate, adverse events, and the predictors associated with the technical failure of ETGBD were investigated. Results: A total of 242 patients were enrolled in the study. The technical success rate of ETGBD and clinical success rate of technically successful ETGBD cases were 87% and 93%, respectively. We experienced cystic duct injury in 24 patients as an ETGBD-related adverse event, and pancreatitis in 12 patients as an endoscopic retrograde cholangiopancreatography-related adverse event. Multivariate analysis indicated that cystic duct injury was the independent predictor associated with the technical failure of ETGBD (odds ratio, 11; 95% confidence interval, 3.9–29; p < 0.001). Conclusions: ETGBD was a safe and effective treatment method for acute cholecystitis with acceptable adverse events. There was no predictor based on the information from patient characteristics; however, cystic duct injury was associated with the technical failure of ETGBD.